2022
DOI: 10.31830/2348-7542.2022.roc-909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest age and storage duration on viability and vigor of shallot (Allium cepa L.) tubers 

Abstract: Shallot is one of the tuber crops used in human life worldwide. Lembah Palu variety of shallot (LPVS) is the best raw material for the fried shallot industry. The main problem is that tubers have no standard harvest age and storage duration to support these plants' germination and early growth. Therefore, shallots' growth and productivity are influenced by tubers' viability and vigor. This study aimed to investigate the harvest age and storage duration to give the best viability and vigor of shallot tubers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This research shows that the maximum storage of shallot bulbs is five months because their growth potential has decreased at the age of 6 months. Ansar et al (2022) found different things in the storage of shallot bulbs, as seeds with a storage duration of 30 days after harvest could be used as planting material. However, the storage period of 60 days had a shorter average growing time of 3.97 days.…”
Section: Percentage Of Rooted and Sprouted Bulbsmentioning
confidence: 99%
“…This research shows that the maximum storage of shallot bulbs is five months because their growth potential has decreased at the age of 6 months. Ansar et al (2022) found different things in the storage of shallot bulbs, as seeds with a storage duration of 30 days after harvest could be used as planting material. However, the storage period of 60 days had a shorter average growing time of 3.97 days.…”
Section: Percentage Of Rooted and Sprouted Bulbsmentioning
confidence: 99%